Expression of TWIST in the first‐trimester trophoblast and decidual tissue of women with recurrent pregnancy losses. (24th March 2017) - Ahn, Jin Hee; Park, Hye Ran; Park, Chan‐Woo; Park, Dong‐Wook; Kwak‐Kim, Joanne
Abstract : Problem: In this study, we aim to investigate if the expression of TWIST in the first‐trimester placenta and decidua has any association with spontaneous abortion (SAB) and recurrent pregnancy losses (RPL). Methods: Expression of TWIST was measured in the first‐trimester trophoblast and decidual tissues using RT‐PCR and immunohistochemistry. Women with a pregnancy loss comprised the study group (AB group) including women with two or more recurrent pregnancy loses (RPL group), and women with a spontaneous abortion who had no history of previous pregnancy losses (SAB group). Controls were women with elective abortion of normal pregnancy (NP group). Results: In in‐vitro culture study of endometrial cells, expression of TWIST was detected with the induction of decidualization. In syncytiotrophoblast, expression of TWIST in NP group was significantly higher than that of AB group. RPL group had no expression of TWIST, both in the nucleus and cytoplasm of syncytiotrophoblast. In decidual tissue, majority of TWIST was expressed on the decidual stromal cells. NP group showed significantly higher expression of TWIST in cytoplasm and nucleus as compared with those of SAB group. Conclusion: This suggests that TWIST may have a functional role in decidualization of endometrial cells and syncytialization of cytotrophoblast cells.